Causes of poor supervision in malay language teaching in primary schools - Subairi Onggoh; Crispina Gregory K. Han; Mohammad Azri Bin Amatan (Human Resource Management Academic Research Society (HRMARS), 2024)
This study examines the teaching practices of Malay Language in primary schools within the Tenom district, focusing on teachers who did not achieve outstanding scores in their Teaching and Learning Practice supervision. The research aims to explore this phenomenon by analysing teaching practices and identifying the factors contributing to these unsatisfactory supervision scores. Consequently, the study proposes recommendations to improve Malay Language teaching practices, helping teachers enhance their teaching and learning implementation. The study is grounded in Danielson's 1996 Framework for Teaching, which includes key components such as planning, classroom environment, instructional approaches, and teachers' professional responsibilities. A qualitative research design with a phenomenological approach was employed. Participants comprised Malay Language teachers selected via purposive sampling based on their teaching supervision scores. Data collection involved interviews, observations, and document analysis, which were subsequently transcribed and analysed using content analysis techniques, aided by Atlas Ti version 22 software. The findings indicate that teachers often plan lessons inadequately, focusing primarily on teaching objectives without considering the diverse knowledge levels of their students. Additionally, they rarely utilize diverse digital teaching materials and infrequently adopt modern instructional approaches, such as 21st-century activities, differentiated learning, digital learning, and edutainment elements.